Clinical outcomes of combined cervical and transthoracic surgical approaches in patients with advanced thyroid cancer. Issue 3 (16th December 2022) - Shenson, Jared A.; Zafereo, Mark E.; Lee, Mark; Contrera, Kevin J.; Feng, Lei; Boonsripitayanon, Mongkol; Gross, Neil; Goepfert, Ryan; Maniakas, Anastasios; Wang, Jennifer Rui; Grubbs, Libby; Vaporciyan, Ara; et al.
Abstract: Background: Advanced thyroid disease involving the mediastinum may be managed surgically with a combined transcervical and transthoracic approach. Contemporary analysis of this infrequently encountered cohort will aid the multidisciplinary team in personalizing treatment approaches. Methods: Retrospective review of patients undergoing combined transcervical and transthoracic surgery for thyroid cancer at a single high‐volume institution from 1994 to 2015. Results: Thirty‐eight patients with median age 59 years (range 28–76) underwent surgery without perioperative mortality. Most patients had primary disease. A majority had distant metastases outside the mediastinum but had locoregionally curable disease. Common complications were temporary (39%) and permanent (18%) hypoparathyroidism, and wound infection (13%). One‐year overall survival was 84%; 1‐year locoregional disease‐free survival was 64%. Median time to locoregional recurrence was 36 months. Only esophageal invasion was associated with worse oncologic outcomes. Conclusions: Combined transcervical and transthoracic surgery for advanced thyroid cancer can be performed without mortality and with acceptable morbidity.